EVALUATING THE INFLUENCE OF TRAIN AXLE LOAD ON RAILWAY BALLAST DEGRADATION AND AXIAL DEFORMATION - MOHAMMED, ASHIRU; Amartey, Yusuf Dada; Murana, ABDULFATAI ADINOYI; Lawan, Adamu (FUDMA Journal of Sciences, 2022)
Degradation and axial deformations of railway ballast bed are highly influenced by stresses induced by moving trains. Hence, this study evaluate the influence of train axle load on the rate of degradation and axial deformation of railway ballast bed. Series of cyclic loading test were conducted at intervals of 200,000 load cycles up to 1,000,000 cycles. Two trains with capacities of 30 ton and 24 tons for freight and passengers respectively were simulated at a typical moving speed of 120 km/hr which is equivalent to a frequency of 16.5 Hz. It was observed that with an increase in both axle load and number of load cycles, the degradation index and the axial deformation increased. It was also observed that ballast degradation has a strong influence on the ballast bed deformation. Hence, ballast degradation is highly influenced by train axle load and the axial deformation of the ballast bed has a strong correlation with the rate of ballast particles degradations